IMPROVING READING COMPREHENSION OF NARRATIVE TEXT THROUGH P-Q-R-S-T STRATEGY AT ELEVENTH-GRADE STUDENTS OF SMA NEGERI 2 TARAKAN - Bid, Sherly Pebriani; Winarno, Winarno (Universitas Borneo Tarakan, 2024)
The purpose of the research was to improve students’ reading comprehension of narrative text through the Preview-Question-Read-Summarize-Test (PQRST) strategy. The research method used was classroom action research. The subjects of this research were students of class XI B SMA Negeri 2 Tarakan in the 2023/2024 academic year which consists of 36 students. There were two cycles in this research. Each cycleconsists of two meetings which include planning, action, observation, and reflection. The instruments used to collect data are tests and observations. In the first cycle, there were 24 students who reached the Learning Objective Achievement Criteria (KKTP) with a percentage of (67%) and 12 students (33%) had not yet reached KKTP. In the second cycle, there were 30 students (84%) who had achieved KKTP and there were 6 students (16%) who did not achieve KKTP. The observation results of teacher and students also improved. The results of teacher observation in the first cycle obtained an average score of 77.5% and increased to 87.5% in the second cycle. It is concluded that the use of the PQRST strategy can enhance students’ reading comprehension of narrative text in class XI B SMA Negeri 2 Tarakan during the2023/2024 academic year. The results of the research suggest that teachers may consider employing the PQRST strategy in teaching, especially teaching reading comprehension.Keywords: Classroom Action Research, Reading Comprehension, PQRST